STUDENTS’ PERCEPTION ON THE USE OF GOOGLE CLASSROOM IN LEARNING ENGLISH AT SMAN 5 JENEPONTO - Titin Andryana B; Nurdin Noni; Amra Ariyani (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aims to determine students' perceptions of the use of Google Classroom in learning English at SMAN 5 Jeneponto. The descriptive qualitative research method was used in this study. The sampling technique is purposive sampling. The data collection technique was conducted by interview using 7 questions conducted with several students. The results showed that the students' perception of using Google Classroom in learning English at SMAN 5 Jeneponto was that most students had negative perceptions of learning English using Google Classroom. This problem is because most students find it difficult to understand online learning materials delivered through applications and students' opinions about the use of Google Classroom in learning English are considered less effective because they cannot improve students' understanding of learning English, do not improve students' English skills and have several obstacles when using Google Classroom.  The obstacles are the quality of the network they have which makes it difficult for them to access Google Classroom and the small size of the video determined by Google Classroom which can make it difficult for students to submit video assignments.